Pengaruh Retun on Asset, Asset Growth, dan Debt to Equity Ratio terhadap Dividend Payout Ratio - Eka Setiajatnika; Kandis Iriani (Jurnal Soshum Insentif, 2018)
The average development of Dividend Payout Ratio in several Manufacturing Sector Companies in Indonesia Stock Exchange period 2012-2016 shows fluctuation. There are several factors related to dividend payout policy such as profit rate, asset expansion rate, and funding requirement. This research uses financial report of 6 (six) manufacturing companies listed in Indonesia Stock Exchange in period 2012-2016 by using comparative descriptive method with quantitative approach and using panel data. The results showed that the Return On Asset and Debt to Equity Ratio partially affect the Dividend Payout Ratio while Asset Growth does not partially affect the Dividend Payout Ratio in the manufacturing sector companies listed on the Indonesia Stock Exchange period 2012-2016. And Return On Asset, Asset Growth, and Debt to Equity Ratio effect simultaneously to Dividend Payout Ratio at manufacturing sector companies listed on Indonesia Stock Exchange period 2012-2016.